2020
DOI: 10.1111/adb.12972
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pituitary adenylate cyclase‐activating polypeptide isoforms in nucleus accumbens subregions on ethanol drinking

Abstract: While limited research has implicated the neuropeptide, pituitary adenylate cyclase‐activating polypeptide (PACAP), in problematic alcohol use, the brain regions and isoforms involved in this effect remain to be determined. One region that has been found both to exhibit PACAP binding and, separately, to be involved in ethanol drinking is the nucleus accumbens (NAc). Thus, this study sought to characterize the effect of the PACAP isoforms in the NAc on ethanol drinking under the intermittent‐access two‐bottle‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
(71 reference statements)
1
10
0
Order By: Relevance
“…As saccharin is not caloric, it is possible that the NAcc Shell shRNA PAC1R knockdown drives animals to increase caloric intake, although this seems unlikely in light of the fact that PACAP effects on hunger are mediated by hypothalamic regions (Resch et al, 2011(Resch et al, , 2014Hurley et al, 2019). Further, it has been previously reported that PACAP administration in the NAcc Shell does not affect sucrose intake (Gargiulo et al, 2021), further supporting the notion that the NAcc PACAP/PAC1R system plays a selective role in the effects of alcohol. Future studies may directly address the question of whether NAcc Shell PAC1R knockdown increases caloric intake.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…As saccharin is not caloric, it is possible that the NAcc Shell shRNA PAC1R knockdown drives animals to increase caloric intake, although this seems unlikely in light of the fact that PACAP effects on hunger are mediated by hypothalamic regions (Resch et al, 2011(Resch et al, , 2014Hurley et al, 2019). Further, it has been previously reported that PACAP administration in the NAcc Shell does not affect sucrose intake (Gargiulo et al, 2021), further supporting the notion that the NAcc PACAP/PAC1R system plays a selective role in the effects of alcohol. Future studies may directly address the question of whether NAcc Shell PAC1R knockdown increases caloric intake.…”
Section: Discussionmentioning
confidence: 78%
“…PACAP modulates the hypothermic effects of alcohol ( Szabó et al, 1998 ; Tanaka et al, 2004 ), and tolerance to acute ethanol-induced ataxia ( Moore et al, 1998 ). Recent reports provide evidence that PACAP-27 and PACAP-38 administration modulate home cage alcohol drinking ( Gargiulo et al, 2021 ), and that ethanol exposure increases PACAP expression in the paraventricular nucleus of the thalamus ( Gupta et al, 2018 ) and in the bed nucleus of the stria terminalis ( Ferragud et al, 2021 ). In human studies, a single nucleotide polymorphism of the gene coding for PACAP, ADCYAP1, was linked to higher levels of alcohol intake in a Finnish population of social drinkers ( Kovanen et al, 2010 ), and a variant of PAC1R was found to be associated with problematic alcohol use in women ( Dragan et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the nucleus accumbens shell, where this PACAP is likely released, injection of PACAP-27 in turn specifically reduces ethanol drinking, while a PACAP receptor antagonist instead increases it (Gargiulo et al, 2020b). These same injections do not affect sucrose drinking or anxiety-like behavior, as measured in a light-dark box and open field (Gargiulo et al, 2020b). These data together suggest that a major role of PACAP in the PVT is the regulation of ethanol drinking via negative feedback.…”
Section: Adenylate Cyclase Activating Polypeptide 1/pituitary Adenylate Cyclase-activating Polypeptidementioning
confidence: 78%
“…Specifically, ethanol drinking in rats leads to a significant increase in levels of PACAP-27 in individual cells across the PVT (Gupta et al, 2018). In the nucleus accumbens shell, where this PACAP is likely released, injection of PACAP-27 in turn specifically reduces ethanol drinking, while a PACAP receptor antagonist instead increases it (Gargiulo et al, 2020b). These same injections do not affect sucrose drinking or anxiety-like behavior, as measured in a light-dark box and open field (Gargiulo et al, 2020b).…”
Section: Adenylate Cyclase Activating Polypeptide 1/pituitary Adenylate Cyclase-activating Polypeptidementioning
confidence: 99%
“…The splice variants of the receptor, the different signaling pathways, and the other routes of action are responsible for the very diverse actions of the peptide. Among others, PACAP has been shown to play a role in several physiological processes, such as micturition [6], cardiac excitability [7], control of body weight [8], respiration [9], pain processes [10], cartilage metabolism [11] as well as addiction and stress-related behaviors [12]. PACAP acts as a growth factor and influences the development of the nervous system as well as peripheral organs.…”
Section: Introductionmentioning
confidence: 99%